Investigating virtual reality navigation in amnestic mild cognitive impairment using fMRI. Issue 2 (3rd March 2016) - Migo, E.M.; O'Daly, O.; Mitterschiffthaler, M.; Antonova, E.; Dawson, G.R.; Dourish, C.T.; Craig, K.J.; Simmons, A.; Wilcock, G.K.; McCulloch, E.; Jackson, S.H.D.; Kopelman, M.D.; et al.
ABSTRACT: Spatial navigation requires a well-established network of brain regions, including the hippocampus, caudate nucleus, and retrosplenial cortex. Amnestic Mild Cognitive Impairment (aMCI) is a condition with predominantly memory impairment, conferring a high predictive risk factor for dementia. aMCI is associated with hippocampal atrophy and subtle deficits in spatial navigation. We present the first use of a functional Magnetic Resonance Imaging (fMRI) navigation task in aMCI, using a virtual reality analog of the Radial Arm Maze. Compared with controls, aMCI patients showed reduced activity in the hippocampus bilaterally, retrosplenial cortex, and left dorsolateral prefrontal cortex. Reduced activation in key areas for successful navigation, as well as additional regions, was found alongside relatively normal task performance. Results also revealed increased activity in the right dorsolateral prefrontal cortex in aMCI patients, which may reflect compensation for reduced activations elsewhere. These data support suggestions that fMRI spatial navigation tasks may be useful for staging of progression in MCI.